Enhancing Fourth-Grade Elementary Students' English Vocabulary through Listening with Received Pronunciation (LWRP) - Budianto, Suhartawan; Huda, Nuril; Sayidah, Nur; Sucipto, Sucipto (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This research aimed to investigate the effectiveness of utilizing Listening with Received Pronunciation (LWRP) in improving the English vocabulary of elementary school pupils. A total of sixty-one fourth-grade students actively participated in the study, undergoing both pre-and post-tests to evaluate the impact of the intervention on their vocabulary skills. The results of the study revealed a notable enhancement in the vocabulary proficiency of students who received instruction through LWRP, as evidenced by their post-test scores surpassing those of their peers who did not receive the same intervention. On average, the LWRP group demonstrated higher levels of vocabulary understanding compared to their counterparts. In conclusion, the findings suggest that incorporating Listening with Received Pronunciation into the instruction of elementary school pupils can be an effective and productive approach to fostering proficiency in English vocabulary acquisition at a young age. This research underscores the importance of innovative teaching methods, such as LWRP, in enhancing language learning outcomes for elementary school students.